Accounting for Men's Refusal of Heterosex: A Story-Completion Study With Young Adults. Issue 1 (2nd January 2019) - Beres, Melanie Ann; Terry, Gareth; Senn, Charlene Y.; Ross, Lily Kay
Abstract : In the present study we bring together theory regarding the construction of heterosexuality and masculinities to understand the shifting and changing terrain of heterosexual sex (heterosex). We use inductive qualitative content analysis of story completion data to discover the different ways that heterosex is constructed by the male and female respondents in scenarios where women initiate sex and men, at first, refuse. The stories represented a spectrum of responses that reify and subvert dominant understandings of heterosex. Five major themes were generated from the current data (1) men should initiate sex, (2) he wants to take it slowly, (3) it is natural for men to want sex, (4) it is men's job to look after women, and (5) coercion. We discuss in detail the dominant narratives described by women and men and how they may be shifting. The study thus provides a rich, experience-based representation of heterosexual sexual activity and suggests subtle shifts in how masculinity is managed within heterosexual relationships.